Relaxation-compensated APT and rNOE CEST-MRI of human brain tumors at 3 T - Görke, Steffen; Söhngen, Yannick; Deshmane, Anagha; Zaiss, Moritz; Breitling, Johannes; Boyd, Philip S.; Herz, Kai; Zimmermann, Ferdinand; Klika, Karel D.; Schlemmer, Heinz-Peter; Paech, Daniel; Ladd, Mark E.; et al. (Magnetic resonance in medicine, 2019)
Purpose Relaxation-compensated CEST-MRI (i.e., the inverse metrics magnetization transfer ratio and apparent exchange-dependent relaxation) has already been shown to provide valuable information for brain tumor diagnosis at ultrahigh magnetic field strengths. This study aims at translating the established acquisition protocol at 7 T to a clinically relevant magnetic field strength of 3 T. Methods Protein model solutions were analyzed at multiple magnetic field strengths to assess the spectral widths of the amide proton transfer and relayed nuclear Overhauser effect (rNOE) signals at 3 T. This prior knowledge of the spectral range of CEST signals enabled a reliable and stable Lorentzian-fitting also at 3 T where distinct peaks are no longer resolved in the Z-spectrum. In comparison to the established acquisition protocol at 7 T, also the image readout was extended to three dimensions. Results The observed spectral range of CEST signals at 3 T was approximately ±15 ppm. Final relaxation-compensated amide proton transfer and relayed nuclear Overhauser effect contrasts were in line with previous results at 7 T. Examination of a patient with glioblastoma demonstrated the applicability of this acquisition protocol in a clinical setting. Conclusion The presented acquisition protocol allows relaxation-compensated CEST-MRI at 3 T with a 3D coverage of the human brain. Translation to a clinically relevant magnetic field strength of 3 T opens the door to trials with a large number of participants, thus enabling a comprehensive assessment of the clinical relevance of relaxation compensation in CEST-MRI.
Gesehen am 22.11.2019